Core material of reverse secondary film coating product and preparation method of reverse secondary film coating product
By using the core material-wall material interface tension reinforcement agent and reverse secondary membrane technology in the preparation of food explosion, the quality problem of existing explosive beads in low-temperature environments and the unreasonable packaging problem of core liquid viscosity. Realize higher finished products and better oral experiences.
Patent Information
- Application Number
- CN202411614333.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-24
AI Technical Summary
The cortex of existing food beads is prone to quality problems such as rubber rupture, collapse, and collapse in low-temperature environments, resulting in unusability. At the same time, some inner core liquids have a high viscosity and cannot effectively wrap the outer rubber made of plant rubber substances.
In the process of using the core material-wall material interface tension, in the process of preparing the reverse secondary membrane product, it is used through the double-layer drip head to increase the interface tension of the core material and the wall material. The secondary membrane technology adsorb the core material interface tension reinforcement agent to the inner layer of the wall material to achieve a better package effect.
It effectively improves the yield of blasted beads, reduces the adverse effects of core material viscosity on dripping, and improves the oral melting speed and oral experience.
Smart Images

Figure CN119344476A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food processing and preparation, in particular to a method for preparing a reverse secondary film-coated product core material and a reverse secondary film-coated product. Background Art
[0002] The popping beads are composed of a hard cortex and a core liquid. The main function of the cortex is to prevent the loss of the essence and to support and protect the popping beads from being damaged. The cortex of the popping beads is usually made of plant gums. When the environment changes, especially when the plant gums are stored or used in winter or low temperature environments, the rubber will crack, collapse, collapse and other quality problems, making the popping beads unusable.
[0003] The outer rubbers permitted by law for use in food popping beads mainly include gelatin, carrageenan, xanthan gum, pectin, etc. However, due to the high viscosity of some inner core liquids, it is impossible to wrap the inner core liquid with the outer rubber. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a core material of a reverse secondary laminated product and a method for preparing the reverse secondary laminated product.
[0005] The invention provides an application of a core material-wall material interfacial tension enhancer in the preparation of a reverse secondary film-coated product.
[0006] The invention provides a core material of a reverse secondary film-coated product. The core material of the reverse secondary film-coated product contains a core material-wall material interfacial tension enhancer.
[0007] The invention provides a method for preparing a reverse secondary film-coated product, which comprises: using a double-layer dripper for dripping, immersing the double-layer dripper in a cooling liquid, and then extruding an inner core material and an outer wall material through a concentric dripper, and then dripping them into the cooling liquid for cooling and solidification.
[0008] The present invention has the following beneficial effects:
[0009] The present invention provides a core material of a reverse secondary laminated product and a method for preparing a reverse secondary laminated product. The core material of the reverse secondary laminated product provided by the present invention contains a core material-wall material interfacial tension enhancer. The core material-wall material interfacial tension enhancer can increase the interfacial tension between the core material and the adhesive material, thereby improving the yield rate of the dripping process. The adverse effect of the viscosity of the core material on the dripping process is reduced, thereby improving the yield rate. The prepared reverse secondary laminated product has a better oral melting speed and provides a better oral experience. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0011] Figure 1 The Ca value of the popping beads prepared in Example 1 changes with time;
[0012] Figure 2 This is a graph showing the change of Ca value of the popping beads prepared in Example 2 over time;
[0013] Figure 3 The Ca value of the popping beads prepared in Example 3 changes with time;
[0014] Figure 4 The Ca value of the popping beads prepared in Example 4 changes with time;
[0015] Figure 5 This is a graph showing the change in Ca value of the explosive beads prepared in Example 5 over time. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0017] The following is a detailed description of a core material of a reverse secondary laminated product and a method for preparing a reverse secondary laminated product provided in an embodiment of the present invention.
[0018] In a first aspect, an embodiment of the present invention provides a use of a core material-wall material interfacial tension enhancer in the preparation of a reverse secondary laminated product.
[0019] During the preparation process of products assembled from core materials and wall materials, the selection of core materials and wall materials is limited due to the influence of the viscosity of the core material. For example, during the preparation of explosive beads, the viscosity of the oil solvent that constitutes the core material is relatively large, resulting in the inability to obtain explosive beads by dripping. How to improve and break through this limitation is an urgent problem to be solved.
[0020] The inventor has provided a method for preparing a reverse secondary coating product by using a core material-wall material interfacial tension enhancer. In the process of preparing a popping bead assembled from a core material and a wall material, the use of a core material-wall material interfacial tension enhancer can increase the interfacial tension between the core material and the wall material, and as a reverse secondary coating material, after successful dripping, the popping bead semi-product is collected and placed in a special rotating cage, and the core material-wall material interfacial tension enhancer in the core material will be adsorbed on the inner layer of the wall material and integrated into the wall material in a reverse secondary coating manner. This reverse secondary coating technology can expand the range of wall material choices and provide more options for the development of popping bead wall materials.
[0021] In some optional embodiments, the core material-wall material interfacial tension enhancer includes at least one of modified starch, rubber powder, high-efficiency water-holding agent powder, sugar or sugar alcohol powder, and water-soluble fruit powder;
[0022] Optionally, the diameter of the core material-wall material interfacial tension enhancer is less than 0.15 mm. After many practical verifications, using one or more of modified starch, rubber powder, high-efficiency water-holding agent powder, sugar or sugar alcohol powder, and water-soluble fruit powder as the core material-wall material interfacial tension enhancer can increase the interfacial tension between the core material and the wall material and improve the yield of the dripping process. Furthermore, the core material-wall material interfacial tension enhancer also has a certain water absorption. Adding the core material-wall material interfacial tension enhancer to the popping beads can enhance the water holding capacity of the popping beads, making the prepared popping beads easier to melt and improving the oral experience.
[0023] In some optional embodiments, the reverse secondary film-coated product includes at least one of popping beads, soft capsules, soft candies, and oil-containing sauces.
[0024] In the second aspect, an embodiment of the present invention provides a core material for a reverse secondary laminated product, and the core material of the reverse secondary laminated product contains a core material-wall material interfacial tension enhancer. Adding a core material-wall material interfacial tension enhancer to the core material of the reverse secondary laminated product can increase the interfacial tension between the core material and the wall material, and improve the yield of the dripping process. For core materials that cannot be dripped or have poor dripping effects, the above method can quickly and smoothly achieve dripping, thereby preparing a richer variety of popping bead products, which is conducive to its application in more fields such as food, cigarettes, and products containing special active ingredients.
[0025] In some optional embodiments, the core material of the reverse secondary film-coated product includes a grease solvent and a core material-wall material interfacial tension enhancer, and the amount of the core material-wall material interfacial tension enhancer accounts for 0.1-2% of the total amount of the grease solvent. The amount of the core material-wall material interfacial tension enhancer within a suitable range is conducive to improving the success rate of the bead droplet formation. Too low or too high will cause the interfacial tension between the core material and the wall material to be too small or too large, and the wall material cannot wrap the core material.
[0026] In some optional embodiments, the core material-wall material interfacial tension enhancer includes at least one of modified starch, rubber powder, high-efficiency water-holding agent powder, sugar or sugar alcohol powder, and water-soluble fruit powder;
[0027] Optionally, the modified starch includes at least one of modified corn starch, modified potato starch, modified cassava starch, modified rice starch, modified wheat starch, cyclodextrin, distarch phosphate, hydroxypropyl starch, hydroxypropyl distarch phosphate, acid-treated starch, oxidized starch, and oxidized hydroxypropyl starch;
[0028] Optionally, the gum powder includes at least one of gellan gum, pectin, carrageenan, gum arabic, guar gum, alginate, locust bean gum, xanthan gum, agar, konjac gum, and peach gum;
[0029] Optionally, the high-efficiency water-holding agent powder is sodium acrylate powder;
[0030] Optionally, the sugar or sugar alcohol powder includes at least one of glucose, sucrose, galactose, lactose, fructose, maltose, trehalose, fructooligosaccharides, xylo-oligosaccharides, galacto-oligosaccharides, malto-oligosaccharides, lactofructooligosaccharides, mannose, isomalt, sorbitol, galactitol, lactitol, mannitol, and xylitol;
[0031] Optionally, the water-soluble fruit powder includes at least one of cranberry fruit powder, roxburgh fruit powder, strawberry fruit powder, apple fruit powder, prune fruit powder, fig fruit powder, and blueberry fruit powder;
[0032] Optionally, the diameter of the core material-wall material interfacial tension enhancer is less than 0.15 mm.
[0033] The embodiment of the present invention provides a core material of a reverse secondary laminated product, wherein the core material of the reverse secondary laminated product contains a core material-wall material interfacial tension enhancer. The core material-wall material interfacial tension enhancer includes but is not limited to modified starch, rubber powder, high-efficiency water-holding agent powder, sugar or sugar alcohol powder, and water-soluble fruit powder. The core material-wall material interfacial tension enhancer can be used to enhance the core material-wall material interfacial tension.
[0034] In some optional embodiments, the oil solvent includes one or more of algae oil, octanoic acid glyceride, soybean oil, sunflower oil, and fish oil;
[0035] Optionally, the core material of the reverse secondary laminated product also contains other functional substances.
[0036] It is worth mentioning that other required functional substances such as flavors, minerals, vitamins, probiotics, specific or special active ingredients, etc. can also be added to the core material of the reverse secondary laminated product.
[0037] In a third aspect, an embodiment of the present invention provides a method for preparing a reverse secondary laminated product, which includes: using a double-layer dripper for dripping, immersing the double-layer dripper in a coolant, and then extruding an inner core material and an outer wall material through a concentric dripper, and then dripping them into the coolant to cool and solidify.
[0038] In some optional embodiments, the steps include: configuration of inner core material and outer wall material, bead dropping, cooling and shaping, and tumble drying;
[0039] Optionally, the preparation of the core material comprises the following steps: dispersing the core material-wall material interfacial tension enhancer in a grease solvent, homogenizing and shearing, sieving and setting aside, the stirring rate is 10000r / min, and the mesh size of the sieve is 80 meshes;
[0040] Optionally, the preparation of the wall material comprises the following steps: adding water to 20% gelatin, 10% glycerol, and 25% erythritol, and mixing them evenly, stirring and melting at 80° C., with a viscosity of 20-40 cp, and removing bubbles before use;
[0041] Optionally, the dripping of the bursting beads includes the following steps: immersing the double-layer dripper in the coolant, the temperature of the inner core material is controlled at 20-25°C, the pump speed is maintained at 100r / min, the temperature of the outer wall material is controlled at 70-80°C, the pump speed is maintained at 30r / min, the coolant includes at least one of paraffin oil and caprylic acid triglyceride, and the temperature of the coolant is controlled at 10-15°C; the diameter of the dripping bursting beads is controlled at 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm; after the dripping is completed, the semi-product of the bursting beads is collected and placed in a rotary cage dryer, and the rotary cage speed is 80-100r / min; and then dried at 20-25°C and 30% humidity, and the drying is completed when the water activity of the rubber reaches 0.38-0.40. In the process of preparing the bursting beads, controlling the core material, wall material and coolant within a suitable temperature range can achieve smooth dripping of the bursting beads and improve the yield of the bursting beads.
[0042] In some optional embodiments, the reverse secondary coated product includes at least one of popping beads, soft capsules, soft candies, and oil-containing sauces. The reverse secondary coated product has a diameter of 4.5 to 4.8 mm and a rubber thickness of 0.35 to 0.37 mm.
[0043] The present invention will be further described below in conjunction with the embodiments.
[0044] Example 1
[0045] A reverse secondary coating blasting bead comprises the following steps:
[0046] Core solution preparation:
[0047] The oil used in the core liquid is selected from algae oil, octanoic acid glyceride, soybean oil, sunflower oil, and fish oil, and there is no requirement for the mixing ratio. The oil is added to 0-2% (mass ratio) of modified starch powder as a reverse secondary coating material. The diameter of the modified starch particles is less than 0.15mm. The types of modified starch include corn modified starch, potato modified starch, cassava modified starch, rice modified starch, wheat modified starch, cyclodextrin, phosphate distarch, hydroxypropyl starch, hydroxypropyl distarch phosphate, acid-treated starch, oxidized starch, and oxidized hydroxypropyl starch. This experiment takes pure algae oil as the oil phase and corn modified starch as the reverse secondary coating material as an example. A certain amount of corn starch is added to the algae oil, homogenized and sheared at 10,000 r / min, and passed through an 80 sieve for use.
[0048] Preparation of glue:
[0049] Gelatin 20%, glycerin 10%, erythritol 25%, add water and mix evenly, stir and melt at 80℃, the viscosity is 20-40cp, and set aside after removing bubbles.
[0050] Exploding beads dripping system:
[0051] Put the core liquid into the core liquid tank of the pill machine (Yantai Baiyaotai Chinese Medicine Technology Co., Ltd., DWJ-2000-JW model), and control the temperature at 20-25°C; put the glue into the glue tank of the pill machine, and control the temperature at 70-80°C. Use light liquid paraffin as the coolant, and control the temperature at 10-15°C. Use a double-layer dripper for dripping, with a core liquid dropper diameter of 1mm and a glue dropper diameter of 2.5mm. Set the core liquid pump speed to 100r / min, the glue pump drip speed to 30r / min, and the dripper to drip. The diameter of the dripping beads is 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm. Collect the semi-products of the bursting beads and put them into the tumble dryer. The tumbler speed is 80-100r / min, and dry at 20-25°C and 30% humidity. When the water activity of the rubber reaches 0.38-0.40, the drying is completed.
[0052] Experimental results statistics:
[0053] The statistical indicators include three items:
[0054] (1) Defective rate: 10 beads are randomly selected during the dripping process and observed under a microscope. If the core liquid is not completely covered by the rubber liquid, but part of the core liquid appears in the rubber skin, and the diameter of the core liquid in the rubber skin occupies more than one-third of the thickness of the rubber skin, the bead is considered to be a defective product; if the thickness of the rubber skin of the bead is uneven and it can be clearly seen, it is also considered to be a defective product.
[0055] (2) Whether the coating is complete: If the reverse secondary coating material in the core layer is completely dissolved into the rubber, it is qualified; otherwise, it is unqualified.
[0056] (3) Mouthfeel: 10 pills of the finished product were randomly selected and their melting speed in the mouth was evaluated on a 10-point scale. The higher the score, the faster the melting speed in the mouth.
[0057]
[0058]
[0059] Based on the three indicators, the optimal addition amount of corn modified starch in the reverse secondary coating material in this experiment is between 0.1% and 1.5%. Other starch-based reverse secondary coating materials can be given the optimal application range one by one according to this idea, and the present invention gives a range of between 0.1% and 2%.
[0060] Interfacial tension test
[0061] Use an interfacial tension meter to test the interfacial tension between the glue solution and pure algae oil and algae oil with 0.5% corn modified starch added at 55°C. Use the syringe provided by the device to inject the core liquid into the glue solution. When the test is met, test the interfacial tension every 1s until the core liquid is separated from the syringe needle. At the same time, test the viscosity of the core liquid and calculate the ratio Ca of the core liquid viscosity / interfacial tension (core liquid to glue solution). Use Ca value as the ordinate and time as the abscissa. Figure 1 As shown, the Ca value of the group with modified corn starch added was significantly lower than that of the pure algae oil group. At a certain flow rate, the lower the ratio of viscosity to interfacial tension, the smaller the effect of viscosity on the fluid, which is more conducive to the burst bead droplet system.
[0062] Example 2
[0063] A reverse secondary coating blasting bead comprises the following steps:
[0064] Core solution preparation:
[0065] The oil used for the core liquid is selected from algae oil, glyceryl stearate, soybean oil, sunflower oil, and fish oil, and there is no requirement for the mixing ratio. The oil is added to 0-2% (mass ratio) of modified starch powder as a reverse secondary coating material. The diameter of non-animal glue particles is less than 0.15mm. The types of non-animal glue include gellan gum, pectin, carrageenan, gum arabic, guar gum, alginate, locust bean gum, xanthan gum, agar, konjac gum, and peach gum. This experiment takes the oil phase as an equal ratio of glyceryl stearate and soybean oil, and pectin as the reverse secondary coating material. A certain amount of pectin powder is added to the oil phase, homogenized and sheared at 10,000 r / min, and sieved through 80 for use.
[0066] Preparation of glue:
[0067] Add water to 15% gelatin, 5% glycerin and 20% erythritol, mix well, stir and melt at 80℃, remove bubbles and set aside.
[0068] Exploding beads dripping system:
[0069] Put the core liquid into the core liquid tank of the pill machine (Yantai Baiyaotai Chinese Medicine Technology Co., Ltd., DWJ-2000-JW model), and control the temperature at 20-25°C; put the glue into the glue tank of the pill machine, and control the temperature at 70-80°C. Use light liquid paraffin as the coolant, and control the temperature at 10-15°C. Use a double-layer dripper for dripping, with a core liquid dropper diameter of 1mm and a glue dropper diameter of 2.5mm. Set the core liquid pump speed to 100r / min, the glue pump drip speed to 30r / min, and the dripper to drip. The diameter of the dripping beads is 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm. Collect the semi-products of the bursting beads and put them into the tumble dryer. The tumbler speed is 80-100r / min, and dry at 20-25°C and 30% humidity. When the water activity of the rubber reaches 0.38-0.40, the drying is completed.
[0070] Experimental results statistics
[0071] The statistical indicators include three items:
[0072] (1) Defective rate: 10 beads are randomly selected during the dripping process and observed under a microscope. If the core liquid is not completely covered by the rubber liquid, but part of the core liquid appears in the rubber skin, and the diameter of the core liquid in the rubber skin occupies more than one-third of the thickness of the rubber skin, the bead is considered to be a defective product; if the thickness of the rubber skin of the bead is uneven and it can be clearly seen, it is also considered to be a defective product.
[0073] (2) Whether the coating is complete: If the reverse secondary coating material in the core layer is completely dissolved into the rubber, it is qualified; otherwise, it is unqualified.
[0074] (3) Mouthfeel: 10 pills of the finished product were randomly selected and their melting speed in the mouth was evaluated on a 10-point scale. The higher the score, the faster the melting speed in the mouth.
[0075] Reverse secondary coating material addition amount Defective product rate / % Is the coating complete? Taste 0 20 / 5 0.1% 0 completely 7 0.5% 0 completely 8 1.5% 0 Incomplete 6 2% 0 Incomplete 6
[0076] Based on the three indicators, the optimal addition amount of pectin in the reverse secondary coating material in this experiment is between 0.1% and 0.5%. Other non-animal glue reverse secondary coating materials can be given the optimal application range one by one according to this idea, and the present invention gives a range of between 0.1% and 2%.
[0077] Interfacial tension test
[0078] Use an interfacial tension meter to test the interfacial tension of the glue solution and the mixed oil, or the mixed oil with 0.1% pectin powder at 55°C. Use the syringe provided by the device to inject the core liquid into the glue solution. When the test is met, test the interfacial tension every 1s until the core liquid is separated from the syringe needle. At the same time, test the viscosity of the core liquid and calculate the ratio of the core liquid viscosity / interfacial tension (core liquid to glue solution) Ca, with the Ca value as the ordinate and the time as the abscissa. Figure 2 As shown in the figure, the Ca value of the popping beads in the group with added pectin powder is significantly lower than that in the mixed oil group. At a certain flow rate, the lower the ratio of viscosity to interfacial tension is, the smaller the effect of viscosity on the fluid is, which is more conducive to the popping bead dripping.
[0079] Example 3
[0080] A reverse secondary coating blasting bead comprises the following steps:
[0081] Core solution preparation:
[0082] The oil used in the core liquid is selected from algae oil, octanoic acid glyceride, soybean oil, sunflower oil, fish oil or one or more mixtures, and there is no requirement for the mixing ratio. The oil is added with 0-0.1% (mass ratio) of a high-efficiency water-holding agent as a reverse secondary coating material, and the particle diameter of the high-efficiency water-holding agent is less than 0.15mm, and the high-efficiency water-holding agent is sodium acrylate powder. This experiment takes the oil phase as an equal ratio of fish oil and sunflower oil as an example, and a certain amount of sodium acrylate is added to the oil phase, and it is homogenized and sheared at 10000r / min, and then passed through an 80 sieve for use.
[0083] Preparation of glue:
[0084] Add water to 15% gelatin, 5% glycerin and 20% erythritol, mix well, stir and melt at 80℃, remove bubbles and set aside.
[0085] Exploding beads dripping system:
[0086] Put the core liquid into the core liquid tank of the pill machine (Yantai Baiyaotai Chinese Medicine Technology Co., Ltd., DWJ-2000-JW model), and control the temperature at 20-25°C; put the glue into the glue tank of the pill machine, and control the temperature at 70-80°C. Use light liquid paraffin as the coolant, and control the temperature at 10-15°C. Use a double-layer dripper for dripping, with a core liquid dropper diameter of 1mm and a glue dropper diameter of 2.5mm. Set the core liquid pump speed to 100r / min, the glue pump drip speed to 30r / min, and the dripper to drip. The diameter of the dripping beads is 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm. Collect the semi-products of the bursting beads and put them into the tumble dryer. The tumbler speed is 80-100r / min, and dry at 20-25°C and 30% humidity. When the water activity of the rubber reaches 0.38-0.40, the drying is completed.
[0087] Experimental results statistics
[0088] The statistical indicators include three items:
[0089] (1) Defective rate: 10 beads are randomly selected during the dripping process and observed under a microscope. If the core liquid is not completely covered by the rubber liquid, but part of the core liquid appears in the rubber skin, and the diameter of the core liquid in the rubber skin occupies more than one-third of the thickness of the rubber skin, the bead is considered to be a defective product; if the thickness of the rubber skin of the bead is uneven and it can be clearly seen, it is also considered to be a defective product.
[0090] (2) Whether the coating is complete: If the reverse secondary coating material in the core layer is completely dissolved into the rubber, it is qualified; otherwise, it is unqualified.
[0091] (3) Mouthfeel: 10 pills of the finished product were randomly selected and their melting speed in the mouth was evaluated on a 10-point scale. The higher the score, the faster the melting speed in the mouth.
[0092]
[0093]
[0094] Based on the three indicators, the optimal addition amount of sodium acrylate as the reverse secondary coating material in this experiment is between 0.02% and 0.04%.
[0095] Interfacial tension test
[0096] Use an interfacial tension meter to test the interfacial tension of the glue solution and the mixed oil, or the mixed oil with 0.02% sodium acrylate powder at 55°C. Use the syringe provided by the device to inject the core liquid into the glue solution. When the test is met, test the interfacial tension every 1s until the core liquid is separated from the syringe needle. At the same time, test the viscosity of the core liquid and calculate the ratio of the core liquid viscosity / interfacial tension (core liquid to glue solution) Ca, with the Ca value as the ordinate and the time as the abscissa. Figure 3 As shown, the Ca value of the group with sodium acrylate powder added is significantly lower than that of the mixed oil group. At a certain flow rate, the lower the ratio of viscosity to interfacial tension is, the smaller the effect of viscosity on the fluid is, which is more conducive to the burst bead drop system.
[0097] Example 4
[0098] A reverse secondary coating blasting bead comprises the following steps:
[0099] Core solution preparation:
[0100] The oil used in the core liquid is selected from algae oil, octanoic acid glyceride, soybean oil, sunflower oil, fish oil or one or more mixtures, and there is no requirement for the mixing ratio. The oil is added with 0-3% (mass ratio) of sugar or sugar alcohol powder as a reverse secondary coating material, the diameter of the sugar or sugar alcohol particles is less than 0.15mm, and the types of sugar or sugar alcohol particles include glucose, sucrose, galactose, lactose, fructose, maltose, trehalose, oligofructose, oligoxylose, oligogalactose, oligomaltose, oligolactose, mannose, isomalt, sorbitol, galactitol, lactitol, mannitol, and xylitol. In this experiment, the oil phase is pure fish oil and oligofructose powder is used as the reverse secondary coating material. A certain amount of oligofructose is added to the oil phase, and it is homogenized and sheared at 10000r / min, and then passed through an 80 sieve for use.
[0101] Preparation of glue:
[0102] Add water to 15% gelatin, 5% glycerin and 20% erythritol, mix well, stir and melt at 80℃, remove bubbles and set aside.
[0103] Exploding beads dripping system:
[0104] Put the core liquid into the core liquid tank of the pill machine (Yantai Baiyaotai Chinese Medicine Technology Co., Ltd., DWJ-2000-JW model), and control the temperature at 20-25°C; put the glue into the glue tank of the pill machine, and control the temperature at 70-80°C. Use light liquid paraffin as the coolant, and control the temperature at 10-15°C. Use a double-layer dripper for dripping, with a core liquid dropper diameter of 1mm and a glue dropper diameter of 2.5mm. Set the core liquid pump speed to 100r / min, the glue pump drip speed to 30r / min, and the dripper to drip. The diameter of the dripping beads is 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm. Collect the semi-products of the bursting beads and put them into the tumble dryer. The tumbler speed is 80-100r / min, and dry at 20-25°C and 30% humidity. When the water activity of the rubber reaches 0.38-0.40, the drying is completed.
[0105] Experimental results statistics
[0106] The statistical indicators include three items:
[0107] (1) Defective rate: 10 beads are randomly selected during the dripping process and observed under a microscope. If the core liquid is not completely covered by the rubber liquid, but part of the core liquid appears in the rubber skin, and the diameter of the core liquid in the rubber skin occupies more than one-third of the thickness of the rubber skin, the bead is considered to be a defective product; if the thickness of the rubber skin of the bead is uneven and it can be clearly seen, it is also considered to be a defective product.
[0108] (2) Whether the coating is complete: If the reverse secondary coating material in the core layer is completely dissolved into the rubber, it is qualified; otherwise, it is unqualified.
[0109] (3) Mouthfeel: 10 pills of the finished product were randomly selected and their melting speed in the mouth was evaluated on a 10-point scale. The higher the score, the faster the melting speed in the mouth.
[0110] Reverse secondary coating material addition amount Defective product rate / % Is the coating complete? Taste 0 20 / 5 0.1% 10 completely 7 0.8% 0 completely 9 1.5% 0 completely 7 2.3% 0 Incomplete 6 3% 10 Incomplete 6
[0111] Based on the three indicators, the optimal addition amount of oligofructose in the reverse secondary coating material in this experiment is between 0.8% and 1.5%. The optimal application range of other sugar / sugar alcohol reverse secondary coating materials can be given one by one according to this idea, and the range given by the present invention is between 0.1% and 3%.
[0112] Interfacial tension test
[0113] Use an interfacial tension meter to test the interfacial tension of the glue solution and pure fish oil, or mixed oil with 0.1% oligofructose powder at 55°C. Use the syringe that comes with the device to inject the core liquid into the glue solution. When the test is met, test the interfacial tension every 1s until the core liquid is separated from the syringe needle. At the same time, test the viscosity of the core liquid and calculate the ratio of the core liquid viscosity / interfacial tension (core liquid to glue solution) Ca, with the Ca value as the ordinate and the time as the abscissa. Figure 4 As shown, the Ca value of the group with oligofructose powder added was significantly lower than that of the pure fish oil group. At a certain flow rate, the lower the ratio of viscosity to interfacial tension, the smaller the effect of viscosity on the fluid, which is more conducive to the bursting bead drop system.
[0114] Example 5
[0115] A reverse secondary coating blasting bead comprises the following steps:
[0116] Core solution preparation:
[0117] The oil used in the core liquid is selected from algae oil, octanoic acid glyceride, soybean oil, sunflower oil, fish oil or one or more mixtures, and there is no requirement for the mixing ratio. The oil is added to 0-2% (mass ratio) of fruit powder as a reverse secondary coating material. The fruit powder particle diameter is less than 0.15mm, and the fruit powder is completely water-soluble. Its types include cranberry fruit powder, sea buckthorn fruit powder, strawberry fruit powder, apple fruit powder, prune fruit powder, fig fruit powder, blueberry fruit powder and other fruit powders. In this experiment, the oil phase is pure fish oil, and a certain amount of cranberry fruit powder is added to the oil phase as a reverse secondary coating material. It is homogenized and sheared at 10000r / min and passed through an 80 sieve for use.
[0118] Preparation of glue:
[0119] Add water to 15% gelatin, 5% glycerin and 20% erythritol, mix well, stir and melt at 80℃, remove bubbles and set aside.
[0120] Exploding beads dripping system:
[0121] Put the core liquid into the core liquid tank of the pill machine (Yantai Baiyaotai Chinese Medicine Technology Co., Ltd., DWJ-2000-JW model), and control the temperature at 20-25°C; put the glue into the glue tank of the pill machine, and control the temperature at 70-80°C. Use light liquid paraffin as the coolant, and control the temperature at 10-15°C. Use a double-layer dripper for dripping, with a core liquid dropper diameter of 1mm and a glue dropper diameter of 2.5mm. Set the core liquid pump speed to 100r / min, the glue pump drip speed to 30r / min, and the dripper to drip. The diameter of the dripping beads is 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm. Collect the semi-products of the bursting beads and put them into the tumble dryer. The tumbler speed is 80-100r / min, and dry at 20-25°C and 30% humidity. When the water activity of the rubber reaches 0.38-0.40, the drying is completed.
[0122] Experimental results statistics
[0123] The statistical indicators include three items:
[0124] (1) Defective rate: 10 beads are randomly selected during the dripping process and observed under a microscope. If the core liquid is not completely covered by the rubber liquid, but part of the core liquid appears in the rubber skin, and the diameter of the core liquid in the rubber skin occupies more than one-third of the thickness of the rubber skin, the bead is considered to be a defective product; if the thickness of the rubber skin of the bead is uneven and it can be clearly seen, it is also considered to be a defective product.
[0125] (2) Whether the coating is complete: If the reverse secondary coating material in the core layer is completely dissolved into the rubber, it is qualified; otherwise, it is unqualified.
[0126] (3) Mouthfeel: 10 pills of the finished product were randomly selected and their melting speed in the mouth was evaluated on a 10-point scale. The higher the score, the faster the melting speed in the mouth.
[0127] Reverse secondary coating material addition amount Defective product rate / % Is the coating complete? Taste 0 20 / 5 0.1% 0 completely 8 0.6% 0 completely 8 1.1% 0 completely 7 1.6% 10 Incomplete 6 2% 30 Incomplete 6
[0128] Based on the three indicators, the optimal addition amount of cranberry powder in the reverse secondary coating material in this experiment is between 0.1% and 1.1%. The optimal application range of other fruit powder reverse secondary coating materials can be given one by one according to this idea, and the range given by the present invention is between 0.1% and 2%.
[0129] Interfacial tension test
[0130] Use an interfacial tension meter to test the interfacial tension between the glue solution and pure fish oil or mixed oil with 0.1% cranberry powder at 55°C. Use the syringe provided by the device to inject the core liquid into the glue solution. When the test is met, test the interfacial tension every 1s until the core liquid is separated from the syringe needle. At the same time, test the viscosity of the core liquid and calculate the ratio of the core liquid viscosity / interfacial tension (core liquid to glue solution) Ca, with the Ca value as the ordinate and the time as the abscissa. Figure 5As shown in the figure, the Ca value of the group with cranberry powder added was significantly lower than that of the pure fish oil group. At a certain flow rate, the lower the ratio of viscosity to interfacial tension, the smaller the effect of viscosity on the fluid, which is more conducive to the burst bead drop system.
[0131] Comparative Example 1
[0132] Referring to Example 1, microcrystalline cellulose is used as the secondary coating material. Microcrystalline cellulose is insoluble in water and will not be adsorbed on the inner layer of the wall material. The evaluation results are shown in the following table. Microcrystalline cellulose can reduce the defective product rate, but cannot be coated and cannot improve the product taste.
[0133] Reverse secondary coating material addition amount Defective product rate / % Is the coating complete? Taste 0 100 / 5 0.1% 0 Incomplete 5 0.5% 0 Incomplete 5 1.5% 0 Incomplete 5 2% 0 Incomplete 5
[0134] From the above experimental results, it can be seen that the embodiment of the present invention provides a method for preparing a reverse secondary coating product core material and a reverse secondary coating product, which is to put a specific core material-wall material interfacial tension enhancer into the core material to increase the interfacial tension between the core material and the wall material, and use it as a reverse secondary coating material. After successful dripping, the semi-finished bead-blasting products are collected and put into a special rotating cage. The material in the core material will be adsorbed on the inner layer of the wall material and integrated into the wall material in the form of reverse secondary coating. This reverse secondary coating technology can expand the selection range of wall materials, i.e., glue liquid materials, and provide more options for the development of bead-blasting rubber.
[0135] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of core material-wall material interfacial tension enhancer in the preparation of reverse secondary laminated products.
2. The use according to claim 1, characterized in that: The core material-wall material interfacial tension enhancer comprises at least one of modified starch, rubber powder, high-efficiency water-holding agent powder, sugar or sugar alcohol powder, and water-soluble fruit powder; Optionally, the core material-wall material interfacial tension enhancer has a diameter of less than 0.15 mm.
3. The use according to claim 1, characterized in that: The reverse secondary film-coated product comprises at least one of popping beads, soft capsules, soft candies, and oil-containing sauces.
4. A core material of a reverse secondary lamination product, characterized in that: The core material of the reverse secondary laminated product contains the core material-wall material interfacial tension enhancer according to any one of claims 1 to 3.
5. The reverse secondary laminated product core material according to claim 4, characterized in that: The core material of the reverse secondary film-coated product comprises a grease solvent and a core material-wall material interfacial tension enhancer, and the amount of the core material-wall material interfacial tension enhancer accounts for 0.1-2% of the total amount of the grease solvent.
6. The reverse secondary laminated product core material according to claim 5, characterized in that: The core material-wall material interfacial tension enhancer comprises at least one of modified starch, rubber powder, high-efficiency water-holding agent powder, sugar or sugar alcohol powder, and water-soluble fruit powder; Optionally, the modified starch includes at least one of corn modified starch, potato modified starch, cassava modified starch, rice modified starch, wheat modified starch, cyclodextrin, distarch phosphate, hydroxypropyl starch, hydroxypropyl distarch phosphate, acid-treated starch, oxidized starch, and oxidized hydroxypropyl starch; Optionally, the gum powder includes at least one of gellan gum, pectin, carrageenan, gum arabic, guar gum, alginate, locust bean gum, xanthan gum, agar, konjac gum, and peach gum; Optionally, the high-efficiency water-holding agent powder is sodium acrylate powder; Optionally, the sugar or sugar alcohol powder includes at least one of glucose, sucrose, galactose, lactose, fructose, maltose, trehalose, fructooligosaccharides, xylo-oligosaccharides, galacto-oligosaccharides, malto-oligosaccharides, lactofructooligosaccharides, mannose, isomalt, sorbitol, galactitol, lactitol, mannitol, and xylitol; Optionally, the core material-wall material interfacial tension enhancer has a diameter of less than 0.15 mm.
7. The reverse secondary laminated product core material according to claim 5, characterized in that: The oil solvent includes one or more of algae oil, octanoic acid glyceride, soybean oil, sunflower oil, and fish oil; Optionally, the core material of the reverse secondary laminated product also contains other functional substances.
8. A method for preparing a reverse secondary film-coated product, characterized in that: It includes: A double-layer dripper is used for dripping. After the double-layer dripper is immersed in the coolant, the inner core material and the outer wall material are squeezed through the concentric dripper and then dripped into the coolant to cool and solidify.
9. The preparation method according to claim 8, characterized in that: The process includes the following steps: configuration of inner core material and outer wall material, bead dropping, cooling and shaping, and tumble drying; Optionally, the preparation of the core material comprises the following steps: dispersing the core material-wall material interfacial tension enhancer in the grease solvent, homogenizing and shearing at 10000 r / min, and passing through an 80 sieve for later use; Optionally, the preparation of the wall material comprises the following steps: adding water to 20% gelatin, 10% glycerin, and 25% sweetener, and mixing them evenly, stirring and melting at 80° C., with a viscosity of 20-40 cp, and removing bubbles before use; Optionally, the bursting bead dripping process includes the following steps: immersing the double-layer dripper in the coolant, the temperature of the inner core material is controlled at 20-25°C, the pump speed is maintained at 100r / min, the temperature of the outer wall material is controlled at 70-80°C, the pump speed is maintained at 30r / min, the coolant includes at least one of paraffin oil and caprylic / decanoic acid triglyceride, and the temperature of the coolant is controlled at 10-15°C; the diameter of the dripping bursting beads is controlled at 4.5-4.8mm, and the thickness of the rubber is 0.35-0.37mm; after the dripping process is completed, the bursting bead semi-products are collected and put into a rotary cage dryer with a rotary cage speed of 80-100r / min; and then dried at 20-25°C and 30% humidity, and the drying is completed when the water activity of the rubber reaches 0.38-0.
40.
10. The preparation method according to claim 9, characterized in that: The reverse secondary film-coated product comprises at least one of popping beads, soft capsules, soft candies, and oil-containing sauces. The reverse secondary film-coated product has a diameter of 4.5 to 4.8 mm and a rubber thickness of 0.35 to 0.37 mm.
Citation Information
Patent Citations
Water blasting bead and preparation method thereof
CN110973699A
Dried orange peel oil microcapsule and preparation method thereof
CN111820417A
Plant essential oil microcapsule and preparation method thereof
CN114177847A
Edible blasting bead containing EGCG (Epigallocatechin Gallate) and preparation method thereof
CN116268396A
Cigarette blasting bead and preparation method thereof
CN117426554A